Perekayasaan Sosial Pembuatan Akses Jalan Usaha Tani di Subak Gunung Kangin Desa Bangli Kecamatan Baturiti Kabupaten Tabanan - PUTRA, I GEDE JULI KRISTINA; DIARTA, I KETUT SURYA; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Social Engineering of Making Agricultural Road Access in Subak Gunung Kangin Bangli Village Baturiti Subdistrict Tabanan Regency Social engineering of making agricultural road access in Subak Gunung Kangin is an effort to overcome the problem of the road that is less good. The success of making access to agricultur roads is interesting to examine by looking at aspects of social capital that support and social engineering processes. The purpose of research to determine social capital owned by subak and social engineering process. The research location is located in Subak Gunung Kangin, Bangli Village, Baturiti Subdistrict, Tabanan Regency. The analytical method used is qualitative descriptive. The results showed that social capital owned by subak supports social engineering (1) trust; The existence of trust among subak members, subak with kerama adat, subak with road initiator and subak with outsiders; (2) social value; The value of togetherness, the value of mutual cooperation, and the value of volunteerism; (3) social networks; The existence of social relations with karma adat, outsiders and local government. While the social engineering process of making agricultural road access is seen from social engineering indicators; (1) cause of internal changes due to lack of access to roads and external changes of opportunity; (2) agent of change is the initiator of the road; (3) target of internal change is subak and external are external; (4) channel of internal change is paum subak and external is negotiation with outsiders; And (5) strategy of change is a personal approach.